A construção ideológica da escola como antídoto ao estigma "situação de risco" atribuído a crianças e jovens: elementos para uma crítica - Silva, Ana Paula Ferreira da (2005)
The study analyzes some images and opinions that generate a peculiar way of thinking about school, the educational process and its students. As a central point of observation, we have selected the term situation of risk , widely used to distinguish the situation where some students are in. The hypothesis of this investigation is that such arguments, when they happen inside or outside school, form a set of opinions that have reinforced the image of school as the social antidote to the risks inherent in the poverty. However, this school keeps on being a mark, which differentiates and gives a specific status to these children that carry the stigma of situation of risk . As theoretical base we have Martins (2002, 1997), Lahire (2004), Paugam (2003) and Rosemberg (1994, 1993). Referring to the question of stigma, we use Elias (2000) and Goffman (2004, 1988). The ideological construction of school as an antidote was analyzed under the perspective elaborated by Thompson (2002). For the empirical task of observation of school, we use Velho (1989) and Bourdieu (2003). In an elementary public school, seven students whose families collect trash on the streets were observed. They represent a part of what has been socially designated as students in a situation of risk . This project confronts these kids, in the environment where they live, with the set of ideas and opinions about their situation, analyzing how much of these ideas they accept. It is supposed, in a superficial and, sometimes, prejudice way, that the student must realize the situation he is living in. Then, the indicated action is to receive the antidotes to their own impulses: the schooling, communal jobs and participation, diagnoses ideologically propagated as examples to salvation from poverty.